Tricellulin facilitates colorectal cancer metastasis through activation of the TGFβ/SMAD2/3 signalling pathway - Yang, Wenfang; Cheng, Ruoxi; Qin, Mengbin; Pan, Xiaoping; Tan, Yanlin; Feng, Kaoyan; Zhang, Jinxiu; Huang, Jiean (Frontiers in Oncology, 2025)
BackgroundTricellulin belongs to the TAMP family of proteins and is primarily localized at the tricellular tight junctions. While its role in the progression of cancer has been reported, its importance in the progression of colorectal cancer (CRC) remains unclear.ObjectiveThis study aimed to determine the function and mechanism of tricellulin in CRC progression.MethodsThe proteins expression in cells and/or tissues was determined by Western blot, immunohistochemistry staining, and/or RT-qPCR analyses. The biological functions of tricellulin were investigated through in vitro assays (CCK-8, Transwell migration, and colony formation assays) and in vivo xenograft models. Tricellulin was significantly upregulated in CRC tissues compared to adjacent normal tissues. The expression of tricellulin was correlated with poor prognosis in patients with CRC.ResultsIn vitro assays showed that tricellulin enhanced CRC cell proliferation, migration, and invasion. Mechanistically, tricellulin activated the TGFb1/SMAD2/3 pathway, while TGFb1 reciprocally controlled the expression of tricellulin. Also, tricellulin promotes CRC cell migration/invasion through EMT. In vivo models confirmed that the overexpression of tricellulin facilitated tumor growth and activated the TGFb1/ SMAD2/3 pathway in CRC.ConclusionOur findings demonstrate thatTricellulin promotes the metastasis of colorectal cancer by activating the TGF-β/SMAD2/3 signaling pathway, and TGF-β1 can reciprocally regulate the expression of tricellulin.We have revealed a novel mechanism by which tricellulin forms a positive feedback loop to promote the growth and metastasis of CRC. This mechanism provides novel insights into CRC progression and suggests potential therapeutic targets.